The integrated behavioral model of mental health help seeking (IBM-HS): A health services utilization theory of planned behavior for accessing care - Hammer, Joseph H; Vogel, David L; Grzanka, Patrick R; Kim, Nayeon; Keum, Brian T; Adams, Claire; Wilson, Sarah A (Journal of counseling psychology, 2024)
This article introduces the integrated behavioral model of mental health help seeking (IBM-HS), a theoretical model for understanding the constructs (e.g., systemic, predisposing, and enabling factors; mental health literacy; illness perceptions; perceived need; stigma; shame; perceived benefits, motivation) that influence people's decision making around seeking professional mental health care and their ultimate access to formal treatment. The IBM-HS is a help-seeking-specific adaptation of the empirically supported integrated behavioral model and integrative model, which are themselves evolutions of the theory of planned behavior and theory of reasoned action. The IBM-HS posits that help-seeking determinants (e.g., structural forces; cultural influences; past help-seeking experience; evaluated need; mental health perceptions, knowledge, and skills; social support) influence help-seeking beliefs (i.e., outcome beliefs, experiential beliefs, beliefs about others' expectations, beliefs about others' behavior, logistical beliefs), which in turn determine their respective help-seeking mechanisms (i.e., attitude, perceived norm, personal agency). These mechanisms collectively influence help-seeking intention, which drives prospective help-seeking behavior, subject to the moderating effects of determinants. Finally, prospective behavior has reciprocal feedback loop effects on certain determinants and beliefs. This article describes the need for the IBM-HS, the model's constructs and their interrelations, measurement considerations, and how the model can be used by scholarly and applied users to systematically understand people's intention to seek professional mental health care services and what helps or hinders them from utilizing this care. (PsycInfo Database Record (c) 2024 APA, all rights reserved).